Portrait of Johannes Wislicenus - Brokesch, Georg (1902)
Portrait of Johannes Wislicenus (1835-1902). Wislicenus was a German organic chemist, known for his work in stereochemistry. He was a professor at the University of Zürich, the Swiss Polytechnical Institute, the University of Würzburg, and the University of Leipzig.
Keywords: Carte de visite photographs; Chemists; College teachers; Wislicenus, Johannes, 1835-1902; Brokesch, Georg Conrad Adolph, 1849-1896